Socioeconomic differences in the menopausal experience of Chinese women. (September 2014) - Huseth-Zosel, Andrea; Strand, Mark; Perry, Judith
Objective: This study explores the effect of employment status, occupation and education on menopausal symptoms experienced by women in an urban community in China. Study design: Cross-sectional survey. Main outcome measures: Menopausal symptoms, medication/supplement use to relieve menopausal symptoms, sociodemographic variables. Results: Risks for more burdensome menopausal symptoms include less education, non-white collar occupation and unemployment/retirement status. Being employed in a white collar occupation and having higher formal education were protective for hot flashes, dry skin/eyes, heart palpitations and insomnia and were associated with increased usage of medication to alleviate menopausal symptoms. Conclusions: As Chinese women age and continue working longer, they will spend increasing amounts of time postmenopausal and in the workplace. The development of worksite-based health programmes would be advantageous to female workers of menopausal age in China.